European Forest Cover During the Past 12,000 Years: A Palynological Reconstruction Based on Modern Analogs and Remote Sensing - Zanon, Marco; Davis, Basil A. S.; Marquer, Laurent; Brewer, Simon; Kaplan, Jed O. (Frontiers in Plant Science, 2018)
Characterization of land cover change in the past is fundamental for understanding the evolution and present state of the earth system, the amount of carbon and nutrient stocks in terrestrial ecosystems, and the role played by land-atmosphere interactions in influencing climate. The estimation of land cover changes using palynology is a mature field, as thousands of sites in Europe have been investigated over the last century. Nonetheless, a quantitative land cover reconstruction at continental scale has been largely missing. Here we present a series of maps detailing the evolution of European forest cover during last 12000 years. Our reconstructions are based on the Modern Analogue Technique (MAT): a calibration dataset is built by coupling modern pollen samples with the corresponding satellite-based forest cover data. Fossil reconstructions are then performed by assigning to every fossil sample the average forest cover of its closest modern analogues. The occurrence of fossil pollen assemblages with no counterparts in modern vegetation represents a known limit of analogue-based methods. To lessen the influence of no-analogue situations, pollen taxa were converted into Plant Functional Types prior to running the MAT algorithm. We then interpolate site-specific reconstructions for each timeslice using a four-dimensional gridding procedure to create continuous gridded maps at continental scale. The performance of the MAT is compared against methodologically independent forest cover reconstructions produced using the REVEALS method; MAT and REVEALS estimates are most of the time in good agreement at a trend level, yet MAT regularly underestimates the occurrence of densely forested situations, requiring the application of a bias correction procedure The calibrated MAT-based maps draw a coherent picture of the establishment of forests in Europe in the early Holocene with the greatest forest cover fractions reconstructed between ~8500 and 6000 cal. yr. BP. This forest maximum is followed by a general decline in all parts of the continent, likely as a result of anthropogenic deforestation. The continuous spatial and temporal nature of our reconstruction, its continental coverage and gridded format make it suitable for climate, hydrological, and biogeochemical modelling, among other uses.